The effect of the pandemic on the transition to tertiary education in Chile: A focus on students with disabilities - M. Ignacia Contreras; Suzanne Duryea; Claudia Martínez Alvear (Inter-American Development Bank (IDB), 2023)
Using a rich set of administrative data, we study the effect of the COVID-19 pandemic on the transition to tertiary education for students with disabilities in Chile. Enrollment rates in primary and secondary education in Chile differ by less than 2 percentage points for students with or without disabilities, but there is an approximately 17 percentage point gap in enrollment in tertiary education. Our difference in differences analysis finds that the pandemic significantly decreased the probability of students with disabilities taking the admission test to tertiary education and enrolling in high-quality tertiary institutions, increasing the inequality in tertiary education. While the pandemic affected the transition to higher education for all students in Chile, students with disabilities were more adversely affected. Understanding how the pandemic has affected opportunities for students with disabilities is critical for informing policies of inclusion.
Keywords: I21; I23; I28; J14; 330; inclusive education; transition to tertiary school; students with disabilities